f(x)=(x-1)^2 and g(x)=x^1/2

### 3 Answers | Add Yours

Finding g(f(x)) is the same as subtituting the f(x) function into the variable for g(x) and simplifying. In this case it involves taking the square root of the squared term, thereby cancelling the exponents:

g(f(x)) = [(x-1)^2]^1/2 = (x-1)^1 = x-1

**g o f = x-1**

We'll write the composition of the functions g and f as it follows:

gof(x) = g(f(x))

f(x) = (x-1)^2 and g(x) = sqrt x

We'll replace x by f(x), in the expresison of g(x).

g(f(x)) = g((x-1)^2)

g((x-1)^2) = sqrt [(x-1)^2]

g((x-1)^2) = |x-1|

The result of composition of the functions is:

(gof)(x) = g(f(x)) = |x-1|

The function` f(x)=(x-1)^2` and `g(x)=x^1/2`

`gof(x) = g(f(x))`

= `g((x - 1)^2)`

= `((x - 1)^2)^(1/2)`

= `(x - 1)^(2*1/2)`

= x - 1

The complex function `gof(x) = x - 1`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes